Living Hadis LIVING HADIS: SEBUAH METODE BARU MEMAKNAI HADIS NABI MUHAMMAD SAW MELALUI FENOMENA SOSIAL-KEAGAMAAN DI INDONESIA - Sobri Febrianto; Munawir (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2023)
Living hadith is a product of people’s understanding of a hadith text. Living hadith is a relevant study in Indonesia. This research is qualitative, which is a category of literature research. The approach used by the author is phenomenological and sociological approaches. This research shows that people’s reception of a text is strongly influenced by other elements such as socio-cultural conditions, geography, ethnography, etc. Then in the example, the author interviewed a tradition of living hadith, namely tahlilan, which occurred in the Jama’ah Masjid Al-Fatah, Pasir Kidul, West Purwokerto, Banyumas. According to the Imam of the tahlilan, the spirit of this routine tradition is based on hadith and the Qur’an, so this sample can be a sign that living hadith is inherent and fertile in Indonesian society